2000
DOI: 10.1093/dnares/7.6.331
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Structure of the Nitrogen-fixing Symbiotic Bacterium Mesorhizobium loti

Abstract: The complete nucleotide sequence of the genome of a symbiotic bacterium Mesorhizobium loti strain MAFF303099 was determined. The genome of M. loti consisted of a single chromosome (7,036,071 bp) and two plasmids, designated as pMLa (351,911 bp) and pMLb (208, 315 bp). The chromosome comprises 6752 potential protein-coding genes, two sets of rRNA genes and 50 tRNA genes representing 47 tRNA species. Fifty-four percent of the potential protein genes showed sequence similarity to genes of known function, 21% to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
503
2
20

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 762 publications
(532 citation statements)
references
References 30 publications
7
503
2
20
Order By: Relevance
“…Rhizobial genomes are subdivided into genome regions specific for their life stages, with chromosomal loci expressed during free-living phases in the soil and symbiosis loci expressed inside of host cells [13,14]. Symbiosis loci required for host nodulation and nitrogen fixation are clustered onto large plasmids or genomic islands [15][16][17][18][19], that can be transferred among lineages, presumably via conjugation [20][21][22]. Non-nodulating rhizobia are also common [23,24], and these strains often lack some or all of the characterized symbiosis loci [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobial genomes are subdivided into genome regions specific for their life stages, with chromosomal loci expressed during free-living phases in the soil and symbiosis loci expressed inside of host cells [13,14]. Symbiosis loci required for host nodulation and nitrogen fixation are clustered onto large plasmids or genomic islands [15][16][17][18][19], that can be transferred among lineages, presumably via conjugation [20][21][22]. Non-nodulating rhizobia are also common [23,24], and these strains often lack some or all of the characterized symbiosis loci [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…%GC data: above average (red) and below average (orange). The symbiosis island is marked in blue in the chromosome plot (coordinates 4644792 to 5255766) (Kaneko et al 2000). Some of the most relevant genes in the acid shock response are mapped in the chromosome plot (Color figure online) Table 3 List of genes with higher increased expression (M≥2) upon the acidic shock NCBI gene annotation was used, except for grey-shaded gene descriptions, which are the result of Blast2GO analysis Chr chromosome, pMLa plasmid, pMLb plasmid, − COG not determined a COG category letters according to NCBI functional categories (http://www.ncbi.nlm.nih.gov/COG/grace/fiew.cgi) correlation between exopolysaccharide synthesis and acid tolerance (Chen et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Since the full-genome annotation available for M. loti strain MAFF303099 was published in 2000 (Kaneko et al 2000), most of the genes found to be overexpressed encode unknown or hypothetical proteins. We used Blast2GO (Götz et al 2008) to annotate all differentially expressed genes encoding unknown or hypothetical proteins and STRING (http://stringdb.org) to assign Clusters of Orthologous Groups (COGs) (http://www.ncbi.nlm.nih.gov/COG/) to these newly annotated genes (Szklarczyk et al 2011).…”
Section: Gene Re-annotationmentioning
confidence: 99%
See 2 more Smart Citations